Efficacy of Low Dose Valganciclovir Prophylaxis for Cytomegalovirus Infection in Kidney Transplantation - Ümit Özçelik; Nadir Alpay; Eryiğit Eren; Bora Uslu; Ahmet Cem Yardımcı (Haseki Tıp Bülteni, 2020)

(untitled)
Aim:Valganciclovir is the preferred drug for chemoprophylaxis for the prevention of cytomegalovirus (CMV) infection in kidney recipients. Low-dose (450 mg/day) valganciclovir use is gaining popularity because standard dose (900 mg/day) has negative effect on renal function and side effects such as leukopenia. We present our results with low-dose valganciclovir prophylaxis in kidney recipients.Methods:One hundred thirteen kidney transplant recipients who were operated between 1 December 2017 and 1 September 2018 in İstanbul Aydın University Faculty of Medicine, Training and Research Hospital and İstinye University Training and Research Hospital were retrospectively evaluated. Demographic data, preoperative CMV status, incidence of CMV infection and leukopenia rates were recorded.Results:A total of 113 patients (46 women, 67 men) with a mean age of 42.85 years were evaluated. All the recipients and donors were preoperative CMV IgG-positive. The mean follow-up was seven (6-13) months. In this period, only two (1.76%) CMV infection occurred and treated with intravenous ganciclovir. There were no complications due to CMV infection. There was no leukopenia related with valganciclovir.Conclusion:This study showed that low-dose valganciclovir is an effective prophylaxis for CMV infection in kidney transplantation with CMV-positive donors and recipients. We recommend low-dose valganciclovir due to low incidence of CMV infection found in our study.